PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI PADA PENGGUNA OJEK ONLINE GRABBIKE DI KOTA KUPANG) - Debi Anastasia Manggoa; Markus Bunga; Ronald P C Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This study aims to analyze the influence of the Marketing Mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on the Consumer Purchasing Decisions. The method used in this study is a quantitative method that is done through the stages of data collection, interpretation of data and appearance of results. Data collection techniques in this study are to use questionnaires. The population in this study was all people domiciled in Kupang City who had used online taxi bike of GrabBike. The technique sampling in this study using Non Probability Sampling with the method of Accidental Sampling, the sample used was 100 respondents .This research uses multiple linear regression analysis. The results show that the Product has a significant influence on the Consumer Purchasing Decisions, the Price has a significant influence on the Consumer Purchasing Decisions, the Place has no influence on the Consumer Purchasing Decisions, the Promotion has no influence on the Consumer Purchasing Decisions, the People has no influence on the Consumer Purchasing Decisions, the Process has a significant influence on the Consumer Purchasing Decisions, and the Physical Evidence has a significant influence on the Consumer Purchasing Decisions. The simultaneous test results in this study revealed that all Marketing Mix variables affect the Consumer Purchasing Decisions. Keywords : Marketing Mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) and Consumer Purchasing Decisions